Possible situations that trigger stress in bank employees in the municipality of Ecoporanga-ES (International Seven Journal of Multidisciplinary, 2023)
Introduction: With globalization, the banking model and the modification of the model used by banks, employees began to suffer from influences linked to high competitiveness, greater profit and market positioning, in order to meet the main current demands. Along with this new work model acquired by bank employees, there is also the great possibility that bank employees developed stress at work, causing psychological problems and directly affecting the quality of life of this employee. Objective: to analyze possible stress indicators presented by bank employees in the municipality of Ecoporanga, in the north of the state of Espírito Santo. Methodology: This is a quantitative, exploratory and descriptive research, carried out with bank employees in the municipality of Ecoporanga (ES) with a focus on possible triggering factors of work stress. Results: The characteristics that manifest stress situations are linked to unexpected events, loss of control and symptoms involving sadness, nervousness and stress itself. Work is affecting these workers' lives not only in their workplace, but also in their personal lives; the answers “always or almost always” had a large percentage mainly in questions that were related to not being able to deal with changes and being able to solve accumulations of generated problems. Conclusion: These professionals feel incapable and sad in their daily lives, thus generating stress due to the pressure not only from their superiors, but also their own pressure to make them feel necessary and useful for the company they work for, with a high predisposition to emergence of mental illnesses or disorders.